Integrated analysis of transcriptome and microRNAs associated with exogenous calcium-mediated enhancement of hypoxic tolerance in cucumber seedlings (Cucumis sativus L.) - He, Lizhong; Yan, Jun; Ding, Xiaotao; Jin, Haijun; Zhang, Hongmei; Cui, Jiawei; Zhou, Qiang; Yu, Jizhu (Frontiers in Plant Science, 2023)
Plants often suffer from hypoxic stress due to flooding caused by extreme weather. Hypoxia usually leads to restricted oxygen supply and alters metabolic patterns from aerobic to anaerobic. Cucumber roots are fragile and highly sensitive to damage from hypoxic stress. The purpose of this study was to investigate the regulatory mechanism of exogenous calcium alleviating hypoxic stress in cucumber through transcriptome and small RNAs analysis. Three treatments were performed in this paper, including untreated-control (CK), hypoxic stress (H), and hypoxic stress + exogenous calcium treatment (H + Ca2+). A large number of differentially expressed genes (DEGs) were identified, 1,463 DEGs between CK vs H, 3,399 DEGs between H vs H + Ca2+, and 5,072 DEGs between CK vs H + Ca2+, respectively. KEGG analysis of DEGs showed that exogenous calcium could activate hormone signaling pathways (ethylene, ABA, IAA and cytokinin), transcription factors (MYB, MYB-related, bHLH, bZIP, and WRKY), calcium signaling and glycolysis pathway to mitigating hypoxic stress in cucumber seedlings. Additionally, miRNA and their target genes were detected and predicted between treatments. The target genes of these miRNAs revealed that auxin, cellulose synthase, and mitochondrial ribosomal related genes (Csa2G315390, Csa6G141390, Csa4G053280, and Csa6G310480) probably play in the improvement of the hypoxic tolerance of cucumber seedlings through exogenous calcium application. In short, our data adds new information to the mechanism of exogenous calcium mitigation of hypoxic stress injury in cucumber seedlings at transcriptional and post-transcriptional levels.